Desarrollo del mercado accionario y crecimiento económico: Alguna evidencia para la Argentina - Luis Lanteri (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2013)
– This paper examines the relationship between stock market development and economic growth in case of Argentina's economy. Apply Granger causality and exogeneity tests based on VEC (vector error correction) models with monthly data covering the period 1993:1-2010:8. The results show that the major stock indices of Buenos Aires Stock Exchange Market (MERVAL25 and BURCAP) Granger cause to the estimator of economic activity (EMAE). In turn, both indices could be considered exogenous variables (weak and strong). Both stock indexes may predict future movements of the monthly indicator of economic activity. The results are in line with the theory that states that the development of financial markets impact on economic growth.
Keywords: C1; G1; O4; 330; stock market development; economic growth; VEC models; Granger causality; exogeneity; Aktienmarkt; Wirtschaftswachstum; Kausalanalyse; VAR-Modell; Argentinien